The challenge of hierarchical church polity in the Presbyterian Church in Malawi: A case of the CCAP Blantyre Synod - Zgambo, Humphreys Frackson (Stellenbosch Theological Journal, 2018)
Hierarchical church polity in the CCAP Blantyre Synod operates contrary to basic tenets of the Reformed tradition in Malawi. Hierarchical church government functions in the CCAP Blantyre Synod as a result of technical influences from European church government and method of evangelisation by the Scottish missionaries. The aim of the study is to investigate how the structures of the CCAP Blantyre Synod were established based on hierarchy, compromising the Reformed church tradition and how to restore this legitimate church polity in the synod. In Reformed church polity perspective, Christ is the Head who governs His church and the legitimate church polity must be rooted in the Scripture through the Spirit.